"He stood like one transfixed with thunder": Male Rape and the Punishment of Libertinism in Eliza Haywood's Love in Excess. Issue 3 (3rd July 2019) - Airey, Jennifer L.
ABSTRACT: Midway through Eliza Haywood's Love in Excess, Count D'elmont falls victim to a bed trick at the hands of the sexually aggressive Melantha. While prior critics have overlooked this scene, it is central to Haywood's ideological purpose: the punishment of D'elmont's sexual aggression. He plans to rape Melliora, only to find himself violated in return. The novel creates a parallel between Alovisa's relationship with Baron D'espernay and D'elmont's relationship with Melantha, one that forces D'elmont into a stereotypically female subject position as the victim of sexual assault. A similar pattern will hold throughout the novel as D'elmont's libertine and violent impulses are punished with acts of sexual coercion perpetrated on his person. This essay therefore argues that Love in Excess seeks both to expose sexual double standards and to punish hypermasculinity and male libertinism. It is only when D'elmont has been stripped of his libertine aggression, only when he has experienced the traditionally feminine role in sexual pursuits, that he earns his happily ever after. Acts of sexual assault become, perversely, the instruments by which the novel civilizes male aggression into companionate bliss.